2010
DOI: 10.1039/c0cc03470c
|View full text |Cite
|
Sign up to set email alerts
|

Dual fluorescent labelling of cellulose nanocrystals for pH sensing

Abstract: Cellulose nanocrystals were converted into ratiometric pH-sensing nanoparticles by dual fluorescent labelling employing a facile one-pot procedure. A simple and versatile three-step procedure was also demonstrated extending the number of fluorophores available for grafting. In this method an amine group was introduced via esterification followed by a thiol-ene click reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
173
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(175 citation statements)
references
References 21 publications
1
173
1
Order By: Relevance
“…This corresponds to a crystallinity drop of The amount of grafted fluorophores is very significant and consists of a large increase when compared with the work of Nielsen et al [20] which reported grafted amounts of [24] or 0.02-0.2 μmol/g 5-(4, 6-dichlorotriazinyl) aminofluorescein (DTAF) achieved by Abitbol et al [44] The absorption spectra of the Cz-a-CNC1, Cz-a-CNC2 and Cz-a-CNC3 ( proportional with the absorption peaks while with increasing concentration, e.g. at 0.08 mg/mL, all the emission spectra display almost the same intensity (Figure 8).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This corresponds to a crystallinity drop of The amount of grafted fluorophores is very significant and consists of a large increase when compared with the work of Nielsen et al [20] which reported grafted amounts of [24] or 0.02-0.2 μmol/g 5-(4, 6-dichlorotriazinyl) aminofluorescein (DTAF) achieved by Abitbol et al [44] The absorption spectra of the Cz-a-CNC1, Cz-a-CNC2 and Cz-a-CNC3 ( proportional with the absorption peaks while with increasing concentration, e.g. at 0.08 mg/mL, all the emission spectra display almost the same intensity (Figure 8).…”
Section: Resultsmentioning
confidence: 88%
“…Fluorescent polymers have become increasingly used as an important macromolecular material in the development of sensors, [20,21] as fluorescent probes in chemical sensing, [22,23] or for bio-imaging and labelling in nanomedicine. [24] Karakawa et al…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen et al (2010) demonstrated a versatile synthetic strategy to obtain fluorescent CNCs for pH sensing. The double bond was introduced onto CNCs by esterification, followed by the thiol-ene Michael addition to introduce amine functionality, which further coupled with the succinimidyl ester dyes containing fluorescein-5 0 -isothiocyanate (FITC) and rhodamine B isothiocyanate (RBITC) (Fig.…”
Section: Esterified Cellulose Containing Aliphatic Moietiesmentioning
confidence: 99%
“…12−15 For instance, CNCs' surfaces were chemically modified to append fluorescent molecules 13,16−19 for bioimaging 12 and pH sensing. 20 These modified CNCs were used for protein/enzyme immobilization studies due to their large surface area (150−250 m 2 /g) and nonporous structure. 21−23 CNCs were explored as a potential drug delivery carrier, where they were capable of binding to ionized and hydrophobic drugs and undergoing controlled release.…”
Section: ■ Introductionmentioning
confidence: 99%